UPAYA MENINGKATKAN HIGHER ORDER THINKING SKILLS (HOTS) PESERTA DIDIK MELALUI PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MATA PELAJARAN IPS - Saputra, Dian; Meitriana, Made Ary; Suadnyani, Luh Putu (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to determine efforts to improve students' HOTS abilities through the Problem Based Learning learning model in social science subject, based on the learning carried out in the previous cycle, there are still a lot of students who have not reached the minimum completeness criteria when answering questions at the HOTS cognitive level. The solution to overcome these problems is using the Problem Based Learning (PBL) learning model. In carrying out this classroom action research, the researchers focused on research that aimed to determine whether there was a change in students' higher-order thinking skills through the application of problem-based learning models, and to find out how much the students' higher-order thinking skills increased using problem-based learning models. This classroom action research was conducted in two cycles of activity with each cycle consisting of two learning meetings. The data collection techniques used in this research are observation and test techniques. Based on the results of the classroom action research that has been carried out, it is concluded that the use of problem-based learning models can be used as an effort to improve participants' Higher Order Thinking Skills (HOTS). students in Social Studies class IX.9 SMP Negeri 2 Singaraja for the 2022/2023 academic year. Based on the results of the data analysis conducted, it is known that after being given action, there was a significant increase in HOTS in students from previously only 46.4% of students increased to 71.4% of students who were at the level of thinking skills. ABSTRAKPenelitian ini bertujuan untuk mengetahui upaya untuk meningkatkan kemampuan HOTS peserta didik melalui model pembelajaran Problem Based Learning pada mata pelajaran IPS. Berdasarkan pembelajaran yang dilakukan siklus sebelumnya, masih banyak peserta didik yang belum mencapai kriteria ketuntasan minimum saat menjawab soal-soal dalam level kognitif HOTS. Solusi untuk mengatasi permasalahan tersebut adalah penggunaan model pembelajaran Problem Based Learning (PBL). Keterlaksanaan penelitian tindakan kelas ini, peneliti memfokuskan penelitian yang bertujuan untuk mengetahui adanya perubahan keterampilan berpikir tingkat tinggi peserta didik melalui penerapan model pembelajaran problem based learning, serta mengetahui seberapa besar peningkatan keterampilan berpikir tingkat tinggi peserta didik dengan menggunakan model pembelajaran problem based learning. Penelitian tindakan kelas ini dilakukan dalam dua siklus kegiatan dengan masing-masing siklus terdiri dari dua pertemuan pembelajaran. Adapun teknik pengumpulan data yang digunakan dalam penelitian ini adalah teknik observasi dan tes. Berdasarkan hasil penelitian tindakan kelas yang telah dilaksanakan diperoleh kesimpulan bahwa pemanfaatan model pembelajaran problem based learning dapat digunakan sebagai salah satu upaya untuk meningkatkan Higher Order Thinking Skills (HOTS) peserta didik pada mata pelajaran IPS kelas IX.9 SMP Negeri 2 Singaraja tahun pelajaran 2022/2023. Berdasarkan hasil analisis data yang dilakukan diketahui bahwa setelah diberikan tindakan terjadi peningkatan HOTS yang cukup signifikan pada peserta didik dari yang sebelumnya hanya 46,4% peserta didik meningkat menjadi 71,4% peserta didik yang berada pada keterampilan berpikir tingkat tinggi.